If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 134 = -1u + 216 Reorder the terms: 134 = 216 + -1u Solving 134 = 216 + -1u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add 'u' to each side of the equation. 134 + u = 216 + -1u + u Combine like terms: -1u + u = 0 134 + u = 216 + 0 134 + u = 216 Add '-134' to each side of the equation. 134 + -134 + u = 216 + -134 Combine like terms: 134 + -134 = 0 0 + u = 216 + -134 u = 216 + -134 Combine like terms: 216 + -134 = 82 u = 82 Simplifying u = 82
| 5sec^2x-5secx=0 | | 5x-(9)=4x+3+2x | | 5sec^2x=0 | | -9(x-2)-(12)=0 | | -19.2s-8.4=2.8-3.6s | | p^2-3p+5=0 | | 14(2x+2)=33 | | 42=2x+2 | | 8y-24x=-24 | | 14(2x+2)=12(2x+5) | | 17x^2-30x+8=0 | | ((3x)^3/2)-6=75 | | (dx/d)8ln(x)= | | 8ln(x)= | | 6(y+5)=2(10+3y) | | -15=-0.2 | | 2y^3+3y^2+y-1666=0 | | .8x+.9y=-1.7 | | 7x+5(x+1)=5+12x | | 110-15y=165 | | (y^2-7)(3y^2-6y+7)= | | -24X^2-24x=-288 | | 1L= | | 15-16y=7 | | 15x+0=3 | | 2x^2+2x^2+2x^2=676 | | 4(x-3)+3=-9 | | 2x^2+2x^2+2x^2=54 | | y=5*7-7 | | 125000+65.00x=175.00 | | 125000+65.00x=175000 | | 2x+2x-12=0 |